PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN TINGKAT PERTUMBUHAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2013-2016 - Ulviana Sari, 14.05.52.0064; Parmono Hadi, Teguh (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of profitability, liquidity, leverage and growth rate on dividend policy. The independent variables in this study are profitability, liquidity, leverage and growth. While for the dependent variable in this research is dividend policy. The study sample consisted of 112 manufacturing companies listed on the Indonesia Stock Exchange for the period of 2013-2016. The sampling technique was chosen by purposive sampling. Financial report data from Indonesia Stock Exchange. The method of analysis used in this study is multiple linear regression.The results of this study indicate that profitability has a positive and significant, liquidity has negative and insignificant effect, leverage has negative and insignificant effect, growth rates have a negative and significant effect on dividend policy. Keywords: profitability, liquidity, leverage and growth rate on dividend policy.